Tax Responses in Local Public Finance: The Flypaper Effect at Work - Marko Köthenbürger; Gabriel Loumeau (Center for Economic Studies and ifo Institute (CESifo), 2023)
The transfer elasticity of income tax rates is an important parameter in public finance. Given the significant fiscal autonomy of Swiss municipalities, Switzerland is an ideal setting for examining behavioral responses to tax policy. Using a regression kink design, we find robust causal evidence that transfers have a positive local average treatment effect on municipal expenditures while leaving the income tax rate (and other tax rates) unchanged. Thus, 'money sticks where it hits', providing comprehensive support for the flypaper effect, including with regard to income tax responses.
Keywords: C21; H72; H77; 330; public finance; regression kink design; flypaper effect; transfers